IMPLEMENTASI KEBIJAKAN PEMILIHAN KEPALA DAERAH (PEMILUKADA) DI KABUPATEN WAROPEN TAHUN 2020 - Herman Isak Watopa; Vince Tebay (JURNAL KEBIJAKAN PUBLIK, 2021)
The election of regional heads is a tool to increase public participation in the life of the nation and state and can be regulated through a mechanism of openness and equality for every citizen and is a process of transitioning leaders of a region that involves the real role of the public or the people in a sovereign manner. The objectives of this study: 1. To examine and analyze how the implementation of the Regional Head Election Policy (Pemilukada) in Waropen 2020. 2. To examine and analyze the supporting and inhibiting factors of the Implementation of the Regional Head Election Policy (Pemilukada) in Waropen 2020. The methodology of this research is descriptive qualitative. . The results of this study indicate that the Waropen Regional Head Election was carried out in the following indicators: 1). Standard policy targets. 2). Policy resources. 3). Communication between organizations. 4). Characteristics of the implementing agency. 5). Executor attitude. 6). Social, political and economic conditions. Of these six indicators, the independence and individual organizers of the event are still involved in supporting one of the candidates for the 2020 Regent and Deputy Regent. Conclusion. 1. Standards and policy objectives the statutory provisions in guarding the Regional Head Election are free, general, honest, fair and dignified as regulated in the regulations, but in practice there is a delay in entering the Covid-19 pandemic. 2. Policy resources and implementing characteristics are available both through regulations, but the consistency of the organizers is still questionable. 3. Filling in the composition of people or members of the organizers (KPUD commissioners, PPK/PPD, KPPS and KPU witnesses) is delayed. 4. Late budgeting affects the activities of each stage of the General Election. 5. Logistics and other supporting facilities were delayed. Suggestions: 1. It is hoped that the standards and policy objectives as regulated in the provisions of the legislation related to the Election of Regional Heads are supported by good quality organizers (KPUD, PPK/PPD, PPS and KPPS). 2. It is expected that the provision of policy resources and characteristics of implementers is on time on the indicators. a. Provision of various regulatory policies. b. Office and work administration. c. Fill in the composition of people or members of the organizers (KPUD commissioners, PPK/PPD, KPPS and KPU witnesses). d. Budgeting and e. Logistics and other supporting facilities. 3. It is expected that the attitude of implementers and communication between organizations related to the implementation of the Warope Regional Head Election remains independent or professional and is not involved in the succession of regional heads. 4. It is hoped that the quality of social democracy, health protocols, political maturity and the candidates for the Regent and Deputy Regent do not stipulate the Regional Revenue and Expenditure Budget (APBD).